The sun does shine : an innocent man, a wrongful conviction, and the long path to justice - Hinton, Anthony Ray; Hardin, Lara Love; Rhuday-Perkovich, Olugbemisola (Feiwel and Friends, 2022)
The author shares his story of being wrongfully convicted of two murders and serving nearly thirty years on death row before his conviction was finally overturned. Highlights his journey from anger and hate to peace, forgiveness, and love--which he worked hard to share with his inmates as he lived a life with passion and purpose even as he awaited execution.